Socioeconomic status and glycemic index among punjabis in Kuala Lumpur, Malaysia: possible association with metabolic syndrome - Kaur, Satvinder; Hip, Seng Yim; Abdul Jalil, Rohana; Mohd Yusof, Barakatun Nisak; Jan Mohamed, Hamid Jan (Springer, 2018)
There are only limited reports on Punjabi's health status in Malaysia. This cross-sectional study assessed the prevalence of metabolic syndrome (Mets) and its risk factors among 277 subjects recruited from the Malaysian Punjabi community. Overall prevalence of Mets was 43%, but 61% among females. Subjects classified with Mets had significantly (p < 0.05) higher body mass index, visceral fat and percentage of body fat. Daily carbohydrate and glycemic index (GI) were also higher among Mets subjects (p < 0.05). Logistics regression analysis showed that primary level of education (OR 5.57, CI 1.29-23.97, p = 0.021) was a factor associated with Mets, followed by middle household income (OR 2.30, CI 1.01-5.20, p = 0.046), GI (OR 1.03, CI 1.00-1.06, p = 0.026), and age (OR 1.03, CI 1.00-1.05, p = 0.023). Mets shows high prevalence among the studied Punjabi population, prompting the consideration of adequate preventive measures, primarily among lower socioeconomic groups.